Bilateral agreement for the academic year 2010/2014 Socrates programme higher education (Erasmus) between Universidade Lusíada de Lisboa and Universidad de Córdoba - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Socrates programme. - Erasmus subject area: Psychology.